Real price and wage rigidities in a model with matching frictions - Keith Kuester (European Central Bank (ECB), 2007)
This paper incorporates search and matching frictions in the labor market into a New Keynesian model. In contrast to the literature, the labor market activity takes place in the (Calvo-staggered) price-setting sector. Matching frictions lead price-setting firms to negotiate wage rates with their employees. The negotiation of wages substantially increases strategic complementarity in price-setting among suppliers of differentiated goods. This leads to an increase in real rigidities as in Woodford (2003), which reduces the size of price changes optimally chosen by re-optimizing firms. The same factors which induce smooth inflation also dampen the adjustment of wages in response to shocks. In the search and matching framework this is key for explaining the highly responsive nature of vacancies in the data. Another interesting finding for the Phillips curve is that inflation is not only driven by an output gap but also by an employment gap – a feature usually neglected in empirical research. The modified model matches impulse responses of an SVAR for post Volcker-disinflation US data very well.
Keywords: E31; E24; E32; J63; J64; 330; bargaining; E24; E32; J63; J64; JEL Classification System: E31; Keywords: firm-specific labor; Phillips curve; real rigidities; wage rigidity; Lohnrigidität; New-Keynesian Phillips Curve; Tarifverhandlungen; Offene Stellen; USA